Characterization of (new) romantic relationships of teenagers - Flores-Hernández, Bibiana G. (2021)
The current study synthesizes some of the main contributions from recent research about the new forms and elements of heterosexual romantic relationships that individuals are adopting  uring the adolescent stage. These relationships are currently divided into formal and informal, the existence of the last ones is due to the replacement of the strict traditional environment because many changes that make up the postmodern era which, in turn, involves marked divergences in the process and content in current relationships and different areas of daily life. As a result of the analysis carried out, it is important to mention the limited existence of information about the subject and even more in the new relationships of couple in specific populations such as homosexual, indigenous or rural areas.